Risk Analysis and Management of Road Infrastructure Using A Single Year Funding System in The Mentawai Islands - Utami, Fadhillah Rizky; Hidayat, Benny; Ophyandri, Taufika (Universitas Negeri Padang, 2023)
Roads are the basic infrastructure that humans need most to be able to move from one place to another to meet their daily needs. According to the Central Statistics Agency, the Mentawai Islands area, the percentage of stable roads available in the Mentawai Islands is only around 10%, so that for Road infrastructure development in the Mentawai Islands is the main target for the local government. The funding system provided is mostly a single year funding system. Single year funding is defined as project activities where the work implementation period corresponds to or is equal to one budget year. The development of road infrastructure with a single year funding system in the Mentawai Islands will certainly not be without the name project risk. The aim of this research is to create risk management in road construction with a single year funding system in the Mentawai Islands. The interview method was conducted to informants. There are 15 risks identified for the Mentawai Islands Regency. The highest potential loss obtained from the contractor is the delay in the tender and the risk aggregate from the contractor is IDR. 40,300,000,000,- . The highest potential loss obtained from the owner is a natural disaster and the aggregate risk from the owner is Rp. 26,880,000,000,-. The highest potential loss that can be obtained from the contractor is the delay in the tender and the aggregate risk from the contractor is Rp. 40,300,000,000,- . The highest potential loss that can be obtained from the owner is a natural disaster and the aggregate risk from the owner is Rp. 26,880,000,000,-. The highest potential loss that can be obtained from the contractor is the delay in the tender and the aggregate risk from the contractor is Rp. 40,300,000,000,- . The highest potential loss that can be obtained from the owner is a natural disaster and the aggregate risk from the owner is Rp. 26,880,000,000,-.